Efficacy of Foliar Nutrition on Vegetative and Reproductive Growth of Sunflower (Global Journal of Science Frontier Research, 2016)
The study showed the significant efficacy of foliar application of macro and micronutrients along with the soil test crop responses on all the parameters of sunflower (Helianthus annuus L.) Among nine treatments under study, treatment T 9 (STCR approach + Foliar spray of NPK @ 1% + ZnSO 4 @ 0.5% + FeSO 4 @ 0.5% and B @ 0.2% ) recorded maximum height of plants (191.7cm), number of leaves per plant (22.17), leaf area (17.32 dm 2 ), stem girth (9.97 cm), minimum days to flowering (54), head diameter (28.14 cm) and total dry matter accumulation (108.07 g plant -1 ) followed by the treatment T 3 : STCR approach (Yield target: 25 q/ha) and T 8 : Soil test based NPK (STL) + Foliar spray of NPK @ 1% + ZnSO 4 @ 0.5% + FeSO 4 @ 0.5% and B @ 0.2%. The stem girth (9.97 cm) was found maximum in T 9 followed by the treatment T 3. Maximum gross returns (Rs. 65,257 ha -1 ), net returns (Rs. 42,105 ha -1 ) and B: C ratio (2.82) was found with T 9 (STCR approach + Foliar spray of NPK @ 1% + ZnSO 4 @ 0.5% + FeSO 4
Keywords: sunflower nutrition; STCR; STL; foliar